2009
DOI: 10.1021/la804099z
|View full text |Cite
|
Sign up to set email alerts
|

General Methodology for Evaluating the Adhesion Force of Drops and Bubbles on Solid Surfaces

Abstract: The shortcomings of the current formulation for calculating the adhesion force for drops and bubbles with noncircular contact lines are discussed. A general formulation to evaluate the adhesion force due to surface forces is presented. Also, a novel methodology, that is, IBAFA, image based adhesion force analysis, was developed to allow implementation of the general formulation. IBAFA is based on the use of multiple profile images of a drop. The images are analyzed (1) to accurately reconstruct the contact lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 22 publications
1
88
0
Order By: Relevance
“…As Antonini et al showed in their work [17], for hydrophobic surfaces with static contact angle greater than 90…”
Section: Adhesion Force Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…As Antonini et al showed in their work [17], for hydrophobic surfaces with static contact angle greater than 90…”
Section: Adhesion Force Modelmentioning
confidence: 75%
“…This expression is integrated numerically to obtain the approximated value of the adhesion force at every deformation state [17]. As Antonini et al showed in their work [17], for hydrophobic surfaces with static contact angle greater than 90…”
Section: Adhesion Force Modelmentioning
confidence: 99%
“…However, once a water droplet is placed on an inclined surface, gravity is applied to such a resting droplet. Thus, the contact angle distribution along the contact line must distort in order to resist the droplet motion [19]. The differences in the geometries of the sessile water droplets result in the variations of the shape of the ice bead eventually.…”
Section: Resultsmentioning
confidence: 99%
“…The idea behind the derivation of the Wetting Force Model comes from the work of Antonini et al [75]. The authors investigated experimentally the adhesion force of a droplet sliding down an inclined surface and they derived a methodology for the prediction of this "adhesion" force.…”
Section: Wetting Force Model (Wfm)mentioning
confidence: 99%